A meta-analysis of the distribution of preschool and early childhood attachment as assessed in the strange situation procedure and its modified versions. Issue 2 (4th March 2023) - Deneault, Audrey-Ann; Bureau, Jean-François; Duschinsky, Robbie; Fearon, Pasco; Madigan, Sheri
ABSTRACT: This meta-analysis synthesized the distribution of attachment classifications as coded with the Cassidy-Marvin Preschool Attachment Coding System and the Main-Cassidy Six-Year-Old System. These systems have extended scholars' capacity to measure differences in the developing child-parent attachment relationship, and its sequelae, beyond the infancy period; however, the global distribution of the attachment categories in these systems, and the potential factors influencing this distribution, remain unknown. The meta-analysis included 97 samples ( N = 8, 186 children; 55% boys), mostly drawn from North American or European populations (89%; M = 76% White). Results indicated that the distribution of child-mother attachment was 53.5% secure, 14.0% avoidant, 11.0% ambivalent, and 21.5% disorganized/controlling. Moderator analyses showed that rates of security were lower, and rates of disorganization were higher, in samples of at-risk families, specifically when children were exposed to maltreatment. Variations in the procedure also moderated the distribution. The discussion calls for greater unity around methodological practices.